Review on issues of administration and distribution of Islamic inheritance in Malaysia - Mat Abdullah, Hani Kamariah; Ab Rahman, Suhaimi; Awang, Mohd Daud (Universiti Islam Pahang Sultan Ahmad Shah, 2022)
This study aims to explore the administration and distribution system of Islamic inheritance practised in Malaysia and identifying the appropriate form of federalism. To achieve this objective, the study utilise the qualitative methodology by performing document analysis utilising public record documents comprising of the Official Report of the House of Parliament, rules and regulations, books and journal references sources. It was found that each agency was created with an important role during the settlement process of administration and distribution of inheritance. The establishment of a diversified agency was set up based on a common goal, which was easing the administration and management of retired estate at the Land Office. Thus, this study proposes a collaborative between federal and state institutions of administration and distribution of Islamic inheritance with their own special function and jurisdiction that should be accomplished for the one common goal.